Out-of-office blood pressure: from measurement to control - Baguet, Jean-Philippe (Dove Medical Press, 2012)
Hypertension is an important risk factor for the development of cardiovascular disease, and is a major cause of morbidity and mortality worldwide. Traditionally, hypertension diagnosis and treatment and clinical evaluations of antihypertensive efficacy have been based on office blood pressure (BP) measurements; however, there is increasing evidence that office measures may provide inadequate or misleading estimates of a patient’s true BP status and level of cardiovascular risk. The introduction, and endorsement by treatment guidelines, of 24-hour ambulatory BP monitoring and self (or home) BP monitoring has facilitated more reliable and reproducible estimations of true BP, including the identification of white-coat and masked hypertension, and evaluation of BP variability. In addition, ambulatory BP monitoring enables accurate assessment of treatment effectiveness over 24 hours and both ambulatory and self BP monitoring may lead to better tailoring of therapy according to BP profile and concomitant disease. This review describes the clinical benefits and limitations of out-of-office assessments and their applications for effective management of hypertension and attainment of BP control.